Optical interferometric structures for application in gas sensors - Pustelny, Tadeusz; Maciak, Erwin; Opilski, Zbigniew; Bednorz, Mateusz (Oficyna Wydawnicza Politechniki Wrocławskiej, 2007)
In the paper, a gas optoelectronic sensor based on interferometric structure has been presented. Active polymer Nafion® layer deposited at the top of the optical fibre forms the Fabry–Perot interferometer. Interaction with gas changes the physical properties of sensing layer, hence the interference conditions are fulfilled for different wavelengths. Sensor performance for different humidity levels has been measured. The influence of humidity variations on sensing layer is investigated as well. In order to suppress the moisture induced instability of the sensor different inhibiting layers have been deposited and their performance has been investigated. In the paper, a wide investigation of the sensor in ammonia atmosphere has been shown.
Optica Applicata, Vol. 37, 2007, nr 1-2, s. 187-194
Keywords: optyka; optical fibre sensors; optoelectronic gas sensors; optical interferometric structures